On the Rise India Looks for Leaders to Key Its Expansion - Jenkins, Joyce; Jenkins, Joyce (Center for Creative Leadership, 2005)
Much has changed in India in the past ten years, and it is poised to emerge as a major player in the global economy. But many observers believe that India must further develop its leadership to fulfill its destiny. Here, the CEO of India's largest media conglomerate talks about the changes, choices, and challenges facing leaders in a nation on the brink.